Postsynthetic Modification of Zirconium Metal-Organic Frameworks - Marshall, Ross J.; Forgan, Ross S. (European journal of inorganic chemistry, 2016)
Metal‐organic frameworks (MOFs) have been in the spotlight for a number of years due to their chemical and topological versatility. As MOF research has progressed, highly functionalised materials have become desirable for specific applications, and in many cases the limitations of direct synthesis have been realised. This has resulted in the search for alternative synthetic routes, with postsynthetic modification (PSM), a term used to collectively describe the functionalisation of pre‐synthesised MOFs whilst maintaining their desired characteristics, becoming a topic of interest. Advances in the scope of reactions performed are reported regularly; however reactions requiring harsh conditions can result in degradation of the framework. Zirconium‐based MOFs present high chemical, thermal and mechanical stabilities, offering wider opportunities for the scope of reaction conditions that can be tolerated, which has seen a number of successful examples reported. This microreview discusses pertinent examples of PSM resulting in enhanced properties for specific applications, alongside fundamental transformations, which are categorised broadly into covalent modifications, surface transformations, metalations, linker and metal exchange, and cluster modifications. The chemical and mechanical stabilities of zirconium metal‐organic frameworks (MOFs) make them ideal platforms for postsynthetic modification. This microreview provides an overview of the various techniques for modification and the functionalities that can be incorporated into zirconium MOFs to facilitate different applications.